Analisis Program TPDS dalam Meningkatkan Kedisiplinan Siswa di SDIT Ar-Ruhul Jadid Jombang - Mahmudah, Siti; Siswanto, M. Bambang Edi (IJPSE Indonesian Journal of Primary Science Education, 2024)
Disciplinary education is an educational process that aims to help students grow and develop attitudes of discipline, obedience and respect in everyday life. Implementing discipline in schools is certainly not enough to just rely on the learning process in the classroom, but there needs to be a special team tasked with enforcing student discipline. This aims to ensure that the application of discipline is more controlled both when students are in class and outside of class, so that students will get used to being disciplined in carrying out any activity. Given this phenomenon, the aim of this research is to find out whether the School Discipline Enforcement Team (TPDS) program has a positive impact on student behavior at Ar-Ruhul Jadid Integrated Elementary School Jombang. This research is a type of narrative descriptive research and is qualitative in nature. Ar-Ruhul Jadid Jombang Integrated Elementary School students from grades one to five were used as research subjects. In this research, observation, interviews and documentation methods were used to collect data. The observation data will be checked up to the data display stage, after which the results will be confirmed and validated. Data from interviews and observations are used as the basis for documentation. The results of research conducted at the Ar-Ruhul Jadid Jombang Integrated Elementary School show the influence of the School Discipline Enforcement Team (TPDS) program on student discipline, including reducing student tardiness, students' ability to comply with regulations, and students' ability to be disciplined with time, worship, rules, and in learning activities. This impact leads to the conclusion that the School Discipline Enforcement Team (TPDS) program can have a very good impact on students, enabling them to develop a disciplinary attitude towards others and themselves.